83. Skin nerve α-synuclein deposits: A biomarker for idiopathic Parkinson's disease. Issue 1 (January 2015) - Donadio, V.; Incensi, A.; Leta, V.; Giannoccaro, M.P.; Scaglione, C.; Cappellari, S.; Avoni, P.; Baruzzi, A.; Liguori, R.
<x xml:space="preserve">Abstract</x> (1) Whether phosphorylated α-synuclein deposits in skin nerve fibers might represent a useful biomarker for idiopathic Parkinson's disease (IPD). (2) The underlying pathogenesis of peripheral neuropathy associated with IPD. We studied 21 well-characterized IPD patients, 20 with parkinsonisms assumed not to have α-synuclein deposits (PAR: 10 vascular parkinsonism, 6 taupathies and 4 parkin mutations) and 30 controls. Subjects underwent: nerve conduction velocities from the leg to evaluate large nerve fibers; skin biopsy from proximal (i.e. cervical) and distal (i.e. thigh and distal leg) sites to study small nerve fibers and deposits of phosphorylated α-synuclein. IPD patients showed a small nerve fiber neuropathy prevalent in the leg with preserved large nerve fibers. PAR patients showed normal large and small nerve fibers. Phosphorylated α-synuclein was not found in any skin sample in PAR patients and controls but it was found in all IPD patients in the cervical skin site. Abnormal deposits were correlated with leg epidermal denervation. Phosphorylated α-synuclein in proximal peripheral nerves is a sensitive biomarker for IPD diagnosis helping to differentiate IPD from other parkinsonisms. Neuritic inclusions of α-synuclein were correlated with a small fiber neuropathy suggesting their direct role in peripheral nerve fiber damage.